DUTA MODERASI BERAGAMA: INOVASI KELEMBAGAAN PENDIDIKAN AGAMA ISLAM DALAM PENGUATAN KARAKTER MODERAT PESERTA DIDIK DI MTSN 1 PASURUAN - Balqisa Ratu Nata; Mudlofir, Ali (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2025)
This study aims to analyze the Religious Moderation Ambassador program as a form of institutional innovation of Islamic Religious Education (PAI) in strengthening the moderate character of students at MTsN 1 Pasuruan. The background of this study is based on the urgent need to strengthen the values ​​of religious moderation amidst the potential for the development of intolerant attitudes in the student environment. Using a qualitative approach with a case study design, data were collected through observation, in-depth interviews with the head of the madrasah, PAI teachers, program supervisors, and religious moderation ambassadors, as well as documentation. The results of the study indicate that this program is implemented systematically through the recruitment of students as ambassadors, religious moderation training, involvement in social and religious activities, and ongoing coaching by PAI teachers. This program is effective in fostering moderate characters such as tolerance, anti-violence, and inclusive attitudes in the daily lives of students. In conclusion, the Religious Moderation Ambassador program is a strategic institutional innovation in internalizing the value of moderation through strengthening the institutional role of PAI. The implications of these findings indicate the importance of replicating similar models in other madrasahs to support the strengthening of character education based on religious moderation.